METABOLIC, ENDOCRIN AND SOCIO -CULTURAL RISK FACTORS IN PATIENTS WITH PRIMARY OSTEOARTHRITIS OF THE KNEE AND RELATIONSHIP WITH RADIOLOGICAL FINDINGS - Nehir Samancı,; Cahit Kaçar,; Meltem Sayın,; Tiraje Tuncer, (Archives of Rheumatology, 2003)
The aim of this study was to investigate some of the risk factors associated with osteoarthritis of the knee and the relationship of these risk factors with radiographic findings. One hundred patients with no known metabolic or inflammatory articular diseases who had a clinical and radiological diagnosis of knee osteoarthritis, and eighteen sex and age matched healthy controls were included in this study. All patients and controls were questioned for accompanying systemic diseases, life style and daily life habits. All patients had undergone physical examination and anthropometric measures were (height, weight, subcutaneous fat tissue) determined. The laboratory parameters like serum glucose, uric acid, lipids, calcium, phosphorus, alkaline phosphotase levels were measured. Radiographic findings were assessed by using the method of Kellegren Lawrence. Weight, body mass index, diabetes mellitus, hypertension, serum glucose and uric acid levels and sedentary life style were significantly higher when compared with healthy controls. A positive correlation was observed between the age, pain, post menopousal duration and centrality ratio and Kellegren Lawrence radiological scores. In conclusion, weight, distrubiton of fat tissue, sedentary life style, some metabolic factors and systemic diseases were determined to be the risk factors for knee osteoarthritis. Determination of modifiable risk factors and avoidance of them may help to decrease the incidence and severity of knee osteoarthritis.